The Notion of Ta’wil (Spiritual Interpretation) in The Tradition of Syī’a Ismā’īliyya: A Study of Al-Sijistānī’s Kitāb Al-Iftikhār - Yusuf Rahman (Refleksi, 2003)
The community of Syi’a Islma’iliyya (Isma’ilis) constitute the second largest Syi’i community after the Twelvers (Syi’a Itsna’asyariyya) in the Muslim world. They live in more then twenty countries of Asia, Africa, Europe and America. Some of its community consider Aga Khan as their spiritual leader in this era.